Germplasm for Dairy Development in East Africa. Phase I: Identifying appropriate germplasm and delivery mechanisms (DGEA1) - Animal Performance - Gibson, John Paul; Mwai, Ally Okeyo; Ojango, Julie; Baltenweck, Isabelle; Rao, E.J.O; Mujibi, Dennis; Poole, Elizabeth; Kemp, Steve (2023)
DGEA will determine what are the most appropriate genotypes for the range of dairy production systems and levels of production operated by small-holder farmers in East Africa, and how these genotypes can be delivered to small-holders. The project partners will apply high density snp technology to determine breed composition of cows owned by small-holders, and combine this with traditional and participatory appraisal of animal and farm performance to determine which genotypes are most profitable at different levels of production. An assessment of the potential value of importing, testing and delivery of genotypes from elsewhere will be undertaken. A partnership will be developed that has a fully articulated business model ready to implement delivery of germplasm in a Phase II project and beyond. A design will also be developed for better delivery of R4D in livestock genetics in sub-Saharan Africa., Germplasm for Dairy Development in East Africa. Phase I: Identifying appropriate germplasm and delivery mechanisms (DGEA1 ). DGEA1 will determine what are the most appropriate genotypes for the range of dairy production systems and levels of production operated by small-holder farmers in East Africa, and how these genotypes can be delivered to small-holders. The project partners will apply high density snp technology to determine breed composition of cows owned by small-holders, and combine this with traditional and participatory appraisal of animal and farm performance to determine which genotypes are most profitable at different levels of production. An assessment of the potential value of importing, testing and delivery of genotypes from elsewhere will be undertaken. A partnership will be developed that has a fully articulated business model ready to implement delivery of germplasm in a Phase II project and beyond. A design will also be developed for better delivery of R4D in livestock genetics in sub-Saharan Africa.